Area of Habitat maps for national key protected wildlife in China - Yinan Yang; Yixuan Yang; Xiangyun Li; Tao Yu; Kejing Pei; Ying Zhong; Yujing Xie (Scientific Data)
Abstract Area of Habitat (AOH) maps depict species distribution patterns, which are essential for predicting species survival, assessing species habitat loss or restoration, and developing biodiversity conservation strategies. AOH maps are generated by extracting suitable elevation ranges and habitat types from species’ geographic range. National Key Protected Wildlife (NKPW) are species protected by Chinese law, playing a critical role in maintaining the country’s biodiversity and ecological security. Currently, publicly available AOH maps provide only single-year AOH data, making it impossible to track temporal changes these areas. We have generated AOH maps for 720 terrestrial NKPW spanning from 1985 to 2022, with a resolution of 30 m. These maps have been independently validated. On average, AOH maps for validated species exhibit a mean point and model prevalence of 0.84 ± 0.20 SD and 0.49 ± 0.27 SD, with 97.03% of species’ AOH maps performing better than random. This long-term, high-resolution dataset of AOH maps provides a valuable resource for biodiversity monitoring and assessment, protected area construction, species extinction risk evaluation, and ecosystem restoration.